Comparative evaluation of formocresol and mineral trioxide aggregate as pulpotomy agents in deciduous teeth - Daya Srinivasan; M Jayanthi (Wolters Kluwer Medknow Publications, 2011)
Aim: To evaluate and compare mineral trioxide aggregate (MTA) and formocresol as pulpotomy medicaments by clinical and radiographic assessments and to assess the histological features of both pulpotomy medicaments in deciduous teeth. Materials and Methods: This study was performed on 100 mandibular deciduous molar teeth requiring pulpotomy treatment. Children between age four and six years were randomly selected and divided into formocresol or MTA group. The patients were recalled after 3, 6, 9, 12 months respectively and evaluated clinically and radiographically. Histological assessment was done on lower deciduous canine teeth, which were undergoing serial extraction for interceptive orthodontic purpose. Pulpotomy was done on four teeth with formocresol and another four teeth with MTA. The teeth were extracted after six months following pulpotomy procedure and histologically evaluated. Two freshly extracted carious teeth were taken as controls. Results: Clinical and radiographic criteria were laid and Chi analysis revealed significant difference in mobility ( P≤0.05), periodontal ligament widening ( P≤0.01 level) and inter - radicular radiolucency ( P≤0.02 level) between two groups at the end of 12 months. Histologically, in MTA group, a layer of new dentine formation with less dentinal tubules at the pulpotomized site was found. In formocresol group, increased inflammatory cells, a zone of atrophy, were noted in radicular portion of pulp. Conclusion: MTA is superior to formocresol clinically, radiographically. Histological analysis showed better reparative ability with hard tissue barrier formation with MTA compared to formocresol.